Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jpcc.1c01701
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Tungsten Doping and Sulfur Vacancies in MoS2 on Enhancement of Hydrogen Evolution

Abstract: Molybdenum sulfide (MoS2) has extensively attracted attention as a promising nonprecious metal catalyst for the electrochemical hydrogen evolution reaction (HER). Nevertheless, synergistically enhancing the intrinsic conductivity and active sites of MoS2 is the pivotal challenge to build up its hydrogen production performance. Herein, a facile ionic liquid-assisted hydrothermal and subsequent annealing treatment strategy is first reported to synthesize W-doped MoS2 nanosheets supported on carbon cloth (Mo1‑x W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
(106 reference statements)
0
16
0
Order By: Relevance
“…To further confirm the successful introduction of S vacancies, an electron paramagnetic resonance (EPR) spectroscopy test was performed, where higher intensities indicate more unpaired electrons and vacancies. As shown in Figure 2f, the EPR spectroscopy provides a typical signal of sulfur vacancies at g=2.003 in 0.5Mo–V 1.11 S 2 and 0.5Mo–V 1.11 S 2‐x while the intensity of 0.5Mo–V 1.11 S 2 is significantly weaker and narrower than that of 0.5Mo–V 1.11 S 2‐x , which confirming that there existed more defects in the 0.5Mo–V 1.11 S 2‐x samples [51–52] . Therefore, based on the above results, we can definitely conclude that Mo‐doped V 1.11 S 2 catalysts with abundant sulfur vacancies were successfully synthesized.…”
Section: Resultsmentioning
confidence: 81%
“…To further confirm the successful introduction of S vacancies, an electron paramagnetic resonance (EPR) spectroscopy test was performed, where higher intensities indicate more unpaired electrons and vacancies. As shown in Figure 2f, the EPR spectroscopy provides a typical signal of sulfur vacancies at g=2.003 in 0.5Mo–V 1.11 S 2 and 0.5Mo–V 1.11 S 2‐x while the intensity of 0.5Mo–V 1.11 S 2 is significantly weaker and narrower than that of 0.5Mo–V 1.11 S 2‐x , which confirming that there existed more defects in the 0.5Mo–V 1.11 S 2‐x samples [51–52] . Therefore, based on the above results, we can definitely conclude that Mo‐doped V 1.11 S 2 catalysts with abundant sulfur vacancies were successfully synthesized.…”
Section: Resultsmentioning
confidence: 81%
“…11 In addition to this, many hierarchal systems have been subjected to electrochemical measurements. [19][20][21][22][23][24][25][26] However, to our knowledge, MoWS 2 is not being used as an electrode for supercapacitors which can beexplored. Herein, to the best of our knowledge, we have demonstrated MoWS 2 and its nanocarbon (MWCNT and rGO)-incorporating hybrids as bifunctional, i.e., electrocatalyst and negatrode, materials for both energy conversion and storage applications for the very rst time.…”
Section: Introductionmentioning
confidence: 99%
“…When the commercial MoS 2 powders were annealed at 100 °C, seven new Raman modes of 198, 222, 352, 486, 516, 815, and 830 cm −1 appear, but two Raman modes of 83 and 95 cm −1 disappear, which indicate that the annealed process could repair the surface defects to avoid activating Mo atoms exposed on the surface and obtain a more ordered Mo—S bond. [ 27 ] Thus, the frequency difference between A 1g and E 1 2g increases to ≈27 cm −1 (Figure 1f). Except for above seven new Raman peaks, the intensity of the remaining peaks decreases with some degree.…”
Section: Resultsmentioning
confidence: 96%
“…The catalytic activity of inorganic metal sulfide can affect the stability of the heterojunction interface and is characterized through the hydrogen evolution reaction that correlated with the number of exposed edge sites with local stoichiometry and a physical and electronic structure. [ 28 ] Some investigations have confirmed that the catalytically active sites of MoS 2 are confined to its edges, [ 27 ] especially at the Mo edge active sites and unsaturated S vacancy sites. [ 29 ] MoS 2 nanosheets with smaller size and higher dispersion could provide much more exposed active edges.…”
Section: Resultsmentioning
confidence: 99%